Optimized Cell Survival and Seeding Efficiency for Craniofacial Tissue Engineering Using Clinical Stem Cell Therapy. (5th November 2014) - Rajan, Archana; Eubanks, Emily; Edwards, Sean; Aronovich, Sharon; Travan, Suncica; Rudek, Ivan; Wang, Feng; Lanis, Alejandro; Kaigler, Darnell
Abstract : This study defined optimized conditions for cell survival and seeding efficiency in the context of tissue engineering and cell-therapy strategies. An autologous stem cell therapy was used to successfully treat a patient with a debilitating craniofacial traumatic deficiency. This clinical report provides a foundation on which to develop more expanded studies using this approach for the treatment of larger numbers of patients with other debilitating conditions to further evaluate efficacy and feasibility. Abstract: : Traumatic injuries involving the face are very common, yet the clinical management of the resulting craniofacial deficiencies is challenging. These injuries are commonly associated with missing teeth, for which replacement is compromised due to inadequate jawbone support. Using cell therapy, we report the upper jaw reconstruction of a patient who lost teeth and 75% of the supporting jawbone following injury. A mixed population of bone marrow-derived autologous stem and progenitor cells was seeded onto β-tricalcium phosphate (β-TCP), which served as a scaffold to deliver cells directly to the defect. Conditions (temperature, incubation time) to achieve the highest cell survival and seeding efficiency were optimized. Four months after cell therapy, cone beam computed tomography and a bone biopsy were performed, and oral implants were placed to support an engineered dental prosthesis. Cell seeding efficiency (>81%) of the β-TCP and survival during the seeding process (94%) were highest when cells were incubated with β-TCP for 30 minutes, regardless of incubation temperature; however, at 1 hour, cell survival was highest when incubated at 4°C. Clinical, radiographic, and histological analyses confirmed that by 4 months, the cell therapy regenerated 80% of the original jawbone deficiency with vascularized, mineralized bone sufficient to stably place oral implants. Functional and aesthetic rehabilitation of the patient was successfully completed with installation of a dental prosthesis 6 months following implant placement. This proof-of-concept clinical report used an evidence-based approach for the cell transplantation protocol used and is the first to describe a cell therapy for craniofacial trauma reconstruction.